Investigation on Heat Transfer Characteristics of the H-type Finned Tube in Flue Gas with High Content of Ash. (May 2017) - Han, Tao; Wang, Chang'an; Cao, Qi; Chen, Wufeng; Che, Defu
Abstract: H-type finned tube is rarely used in waste heat recovery power generation stations, though it has an efficient heat transfer performance in large thermal power stations (WHRPGs, hereafter). To date, understanding of heat performance of H-type finned tube in WHRPGs is still lacked. The heat transfer characteristics of H-type finned tube in gas with high content of ash in WHRPGs was investigated in practical cement plant in present work. The actual ash deposition pattern was observed meanwhile. The characteristics of heat transfer process including heat transfer coefficient, heat effective coefficient, and flue resistance at gas velocity between 4.5 - 6.5 m·s –1 are obtained. Experimental results show that the heat transfer coefficient increases with gas velocity linearly, the heat effective coefficient nearly keep stable on the other hand, and serious ash-block problem occurs in flow area in the heat exchanger at the gas velocity of 4.5 - 6.5 m·s –1 . The max heat transfer coefficient remain below 10 w·m –2 ·k –1, implying heat performance of H-type finned tube in WHRPGs is possibly inefficient.